Ground penetrating radar mapping in rescue archaeology: a study from pego late Bronze Age settlement, Braga (NW Portugal) - Gonçalves, Luís (2008)
Rescue archaeology, sometimes called preventive or salvage archaeology, is archaeological survey and excavation carried out in areas threatened by, or revealed by, construction or other development. Unlike traditional survey and excavation, these works must be undertaken in the shortest possible time. In these scenarios the use of ground penetrating radar (GPR) allows field archaeologists to quickly discover and map buried archaeological features. This paper describes the use of GPR during a rescue archaeology campaign at the Pego Late Bronze Age settlement, near the city of Braga (NW Portugal). Closely spaced GPR transects were collected in a grid-based approach, covering three different areas from the site, using GSSI Sir 3000 System, with antennae frequency of 400MHz. Wave velocities were determined by reflected wave and Hyperbola-Fitting methods. Measured velocities ranged between 0.12-0.14 m/ns. Amplitude slice-maps of the surveyed grids were produced. The interpretation of these maps indicates the existence of several cultural features from Bronze Age (post holes, pits, small trenches and flat graves) at an approximated depth of 50 cm. The information obtained with this GPR survey proved to be very useful. Amplitude slice-maps produced act as primary data that is going to be used to guide the rescue archaeological excavation. These results are significant because they can provide a template for interpretation of future GPR surveys of Late Bronze Age sites in NW Portugal and even in NW Iberia.